Jesus and "the Daniel code" - G. Thom (Acta Theologica)
It is suggested that Jesus, who understood his Messianic calling in the light of the OT prophecies, utilized their symbolic apocalyptic language in his prophetic discourse. From this perspective Matthew 26:64 sheds important light on the meaning of Matthew 24:30b, i.e. that those who rejected him would realize, within a relatively short period, that He – the Suffering Servant – was indeed the Son of Man of Daniel 7. But Jesus also made some very definite statements in very sober language about the future, which provide an important key for our understanding of the prophetic discourse. While He enumerated a number of signs that would warn his disciples of the approach of God’s judgment on Jerusalem – together constituting “the budding fig tree” – He emphasized, on the other hand, that there will be no signs to warn them of the approach of his parousia.